Attraction and aversion of noctuid moths to fermented food sources coordinated by olfactory receptors from distinct gene families - Xiao-Qing Hou; Dan-Dan Zhang; Hanbo Zhao; Yang Liu; Christer Löfstedt; Guirong Wang (BMC Biology)
Abstract Background Alternative food sources are crucial for the survival and reproduction of moths during nectar scarcity. Noctuid moths make a better use of fermented food sources than moths from other families, while the underlying molecular and genetic basis remain unexplored. As the fermentation progresses, yeasts lysis and the accumulation of metabolic byproducts alter the composition and the volatile release of the sugary substrates. However, it is unclear whether and how this would affect the feeding preference of moths. Results Here, we identified eight compounds abundant in the dynamic volatile profiles of several sugary substrates during yeast fermentation. We showed that the cotton bollworm moths were attracted to the fermented sugary substrates while being repelled when the sugary substrates were over-fermented. The attraction and aversion were respectively mediated by isoamyl alcohol and octanoic acid. We deorphanized the olfactory receptors detecting these two compounds and found that they belonged to two distinct gene families and were functionally conserved across four noctuid subfamilies; HarmOR52 orthologues responded to the attractive isoamyl alcohol and HarmIR75q.1 orthologues responded to the aversive octanoic acid. Conclusions Our findings suggest that this functional conservation is an olfactory adaptation that has allowed noctuid moths to extend their diet to fermented food sources.